2018
DOI: 10.1002/hbm.24460
|View full text |Cite
|
Sign up to set email alerts
|

Does the insula contribute to emotion‐related distortion of time? A neuropsychological approach

Abstract: The literature points to a large distributed brain network involved in the estimation of time.Among these regions, the role of the insular cortex is still poorly understood. At the confluence of emotional, interoceptive, and environmental signals, this brain structure has been proposed to underlie awareness of the passage of time and emotion related time dilation. Yet, this assumption has not been tested so far. This study aimed at exploring how a lesion of the insula affects subjective duration, either in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This idea is defended in the theory of the embodiment of time (Droit‐Volet, ; Effron, Niedenthal, Gil, & Droit‐Volet, ; Wittmann, ), with the insula—an interoceptive region (Craig, )—playing a critical role in duration judgments (Wittmann, van Wassenhove, Craig, & Paulus, ). However, there is no consensus in the literature concerning the key role of the insula in the different forms of time judgments (see Mella et al, ), and the direct link between physiological activity and time judgments has not yet been clearly established, although numerous studies have already shown the effects of the increase of arousal on the judgment of physical durations, namely in emotional contexts (Droit‐Volet, ). Nevertheless, we can agree on the fact that the awareness of the self‐duration is related to the awareness of the embodied self, with a critical role of the insula (Craig, ), but these judgments at the consciousness level are not based on the same mechanisms as those involved in the judgment of short physical durations.…”
Section: Conclusion: What Are the Mechanisms Underlying Time–self Linmentioning
confidence: 99%
“…This idea is defended in the theory of the embodiment of time (Droit‐Volet, ; Effron, Niedenthal, Gil, & Droit‐Volet, ; Wittmann, ), with the insula—an interoceptive region (Craig, )—playing a critical role in duration judgments (Wittmann, van Wassenhove, Craig, & Paulus, ). However, there is no consensus in the literature concerning the key role of the insula in the different forms of time judgments (see Mella et al, ), and the direct link between physiological activity and time judgments has not yet been clearly established, although numerous studies have already shown the effects of the increase of arousal on the judgment of physical durations, namely in emotional contexts (Droit‐Volet, ). Nevertheless, we can agree on the fact that the awareness of the self‐duration is related to the awareness of the embodied self, with a critical role of the insula (Craig, ), but these judgments at the consciousness level are not based on the same mechanisms as those involved in the judgment of short physical durations.…”
Section: Conclusion: What Are the Mechanisms Underlying Time–self Linmentioning
confidence: 99%
“…Moreover, lesions in the mediodorsal nuclei are associated with a decrease in cerebral blood flow in cortical areas, most notably the dorsolateral prefrontal cortex (39, 54), an essential region in time perception circuits. The insula is also involved in the time perception circuit (43,55). Both the anterior portion and posterior part of the insula have been implicated in time perception tasks, with the posterior part being more involved in the encoding phase of time perception tasks and the anterior part more involved in the reproduction phase where an explicit judgment of duration is made (49,56).…”
Section: Discussionmentioning
confidence: 99%
“…We found time perception deficits to be slightly more common in strokes affecting the right hemisphere (219 vs. 199 in the left hemisphere). Numerous locations were associated with time perception deficits, namely the thalamus ( 38 41 ), insula ( 43 ), basal ganglia ( 42 ), cerebellum ( 21 25 ) and cortical structures (dorsolateral prefrontal cortex ( 24 , 25 , 27 , 28 , 32 , 36 , 44 , 47 ), parietal cortex ( 32 , 36 , 44 47 ), including supramarginal ( 26 , 28 , 33 ) and angular gyri ( 28 ), temporal cortex ( 26 , 32 , 36 , 46 , 47 ). These locations correspond to those commonly reported in time perception studies with functional brain MRI in healthy participants ( 5 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found time perception deficits to be slightly more common in strokes affecting the right hemisphere (219 vs. 199 in the left hemisphere). Numerous locations were associated with time perception deficits, namely the thalamus (38)(39)(40)(41), insula (43), basal ganglia (42), cerebellum (21-25) and cortical structures (dorsolateral prefrontal cortex (24,25,27,28,32,36,44,47), parietal cortex (32, 36, 44-47), including supramarginal (26,28,33) and angular gyri (28), temporal cortex (26,32,36,46,47). These locations correspond to those commonly reported in time perception studies with functional brain MRI in healthy participants (5,49).…”
Section: Discussionmentioning
confidence: 99%